THE INFLUENCE OF EXPERIENTIAL MARKETING ON SELF SERVICE CUSTOMER SATISFACTION - Adabiyah, Siti Layyinatul; Rachmawati, Fitria Dwi; Fawaid, Nurul; Qomariah, Nurul (Univesitas Muhammadiyah Tangerang, 2024)
This research aims to determine the impact of experiential marketing on customer satisfaction at the Madinah Mart Cangkring Jember Store. The population in this study were all buyers at the Madinah Mart Cangkring Jember Store. The planned sample size in this research was determined to be 50 respondents. The independent variables from this research are sense, feel, think, act and relate. Meanwhile, the dependent variable is customer satisfaction. The data analysis that will be used in this research is descriptive analysis, analysis of validity and reliability tests, analysis of research hypothesis testing. The research is expected to produce that the variables sense (X1), feel (X2), think (X3), act (X4) and relate (X5) can provide a significant increase in customer satisfaction at the Madinah Mart Cangkring Jember Store